Phenomenological And Structuralism Paradigm In Javanese Plant Metaphor - Hidayah, Arini; Wijana, I Dewa Putu; Hendrokumoro (Journal of Education for Sustainability and Diversity, 2025)
Metaphor is a form of stylistic or conveying meaning in which a concept or idea is expressed by comparing it with other concepts or ideas that are different. Metaphors implicitly compare two unrelated things to convey a deeper understanding or concept. Specifically, this article presents a discussion of the elements of phenomenological and structural paradigms in Javanese plant metaphor by adopting paradigm theory in cultural sciences. This article reveals that Javanese plant metaphor has a basic principle in how it functions and how meaning is expressed. The main principles of Javanese plant metaphor involve the understanding of the concept of comparison and the use of figurative language aspects. This article specifically discusses the elements of the phenomenological and structuralism paradigm in Javanese plant metaphor. Metaphors explain, enliven, facilitate, and change way of understanding reality. Metaphors vary by context, culture, and communication. Metaphors enhance language clarity and expression.